The use of Information Technologies for the implementation of the statistical analysis of Polymer product prices - Gareeva, Gulnara; Grigoreva, Diana (Revista Publicando, 2017)
A wide introduction of computer technology in all spheres of activity of organizations and enterprises creates the prerequisites for an active use of information technologies to implement the statistical analysis. This article is devoted to the use of information technologies in statistical methods on the example of price analysis for polymer products. The statistical analysis was performed using the "Statistica" software on the basis of available data. In this work they used the method of exponential smoothing and neural network methods of system analysis. On the basis of monthly data, during the period from January 2012 to December 2016, the production volume prediction was developed until December 2017. Comparing the results of two methods application - neural networks and exponential smoothing, it follows that both methods predict the trend of production volume growth, and their greatest volume will be in December 2017. However, in the course of prediction by the method of exponential smoothing, the model showed that in December 2017 the production volume will make just over 125 thousand tons, which is 5 thousand tons more than the selected neural network model showed. At the same time, during the exponential smoothing method, a larger error (5.49%) was observed on the cross-check, than within the model obtained during the application of neural networks (2.47%).